THE DESIGN OF AUDIO DELAY MODULE TO CREATE STAGING AND IMAGING EFFECT - Hans Kristanto; Teng sutrisno (Mechanova, 2015)
Humans have the ability to determine the location of a sound source using two ears as a comparisoncalled sound localization, just like the eyes when viewing a 3D movie. In the car, there are twosources of sound that left and right speakers. Both of these sound sources can lead to the creationof staging and imaging effects. However, unlike the home multimedia system that can be placedsymmetrically to the listener. Therefore, the device needs to set the delivery time of the sound by thespeaker.This research is done by designing a module to determine the accuracy of the module is carried outexperiments using two different power supply. Power supply is contained in the adapter laboratorycontrol system and the battery 9 V. From the research conducted, it was found that there was adifference delay generated IC PT2399 when it gets electricity from the power supply source isdifferent. In this study also found that the time difference of the sound of each speaker to the earaffects the quality of staging and imaging effects, audio systems that use delay has a staging locationin front of the driver.